Essays on networks and market design - Teytelboym, A (2013)
This thesis comprises four essays in the economics of networks and market design. The common thread in all these essays is the presence of complementarities or externalities. Chapter 2 presents a unified model of networks and matching markets. We build on a contribution by Pycia (2012). We show that strong pairwise alignment of agents’ preferences is a necessary and sufficient condition for the existence of strongly stable networks and strongly stable allocations in multilateral matching markets with finite contracts. Strongly stable networks are not necessarily efficient. Although we use a demanding stability concept, strong pairwise alignment allows for complementarities and externalities. In Chapter 3, we generalise the gross substitutes and complements condition introduced by Sun and Yang (2006). Our new condition guarantees the existence of competitive equilibrium in economies with indivisible goods. Competitive equilibrium can be found using an extension of the double-track adjustment process (Sun and Yang, 2009). In this chapter, we also study contract networks (Ostrovsky, 2008). We show that chain-stable contract allocations can exist even in cyclical contractual networks, such as electricity markets, as long as they are appropriately segmented. In Chapter 4, we run a series of experiments to compare the performance of four auctions – first-price, Vickrey, Vickrey-Nearest Rule (Day and Cramton, 2008), and Reference Rule (Erdil and Klemperer, 2010). In our setting, there are two items and three bidders. Two local bidders want an item each, but the global bidder wants both items. We introduce various exposure and package-bidding treatments. We find that the first-price auction always revenue-dominates all the other auctions without any loss in efficiency, strengthening the results of Marszalec (2011). Exposure affects global bidders only in the first-price auction. In other auctions, global bidders often do not take into account the effect of their own bids on their payments. We find no evidence of threshold effects. Finally, in Chapter 5, we develop a new model of online social network formation. In this model, agents belong to many overlapping social groups. We derive analytical solutions for the macroscopic properties of the network, such as the degree distribution. We study the dynamics of homophily – the tendency of individuals to associate with those similar to themselves. We calibrate our model to Facebook data from ten American colleges.